MENINGKATKAN KETERAMPILAN BELAJAR YANG KREATIF DAN EFEKTIF DENGAN WORDWALL - Khotimah, Sonia Puji Nur; Intan, Nur; Viratama, Ika Putra (Cahaya Ilmu Bangsa Institute, 2024)
One effective strategy to increase student learning activity is to apply varied and interactive learning media. This learning media can be packaged in the form of games or educational games that utilize technology such as smartphones or laptops. Want to provide a fun and interactive learning atmosphere. The online game Wordwall could be the solution! This platform offers various types of interesting educational games to increase students' enthusiasm for learning. The hope is that students can enjoy a more open and confident learning process so that students understanding and skills become better. This activity aims to increase teacher creativity and student learning outcomes through the use of online game-based learning media Wordwall. By implementing Wordwall in learning, it is hoped that it can improve the quality of education and produce the nation's next generation who are intelligent and creative. Socialization activities and practice of creating learning questions in the form of games using the Wordwall application have proven effective in improving teacher abilities. This is proven by the results of activities which show that the majority of teachers have mastered the use of the Wordwall application and understand its benefits in learning.